ANALISIS PRODUKTIVITAS TAMBAK UDANG VANNAME (LITOPANAEUS VANNAMEI) SEMI INTENSIF DI TIGA PROVINSI DALAM PULAU JAWA - Akhmad Salis Nifdhol Salis; Aminin; Farikhah (Techno-Fish, 2023)
Vannamei shrimp cultivation in Indonesia is currently the mainstay of the aquaculture sector and is a priority for aquaculture development in Indonesia to improve the national economy. Pond management in general in Indonesia, especially in Java, still needs better management planning. This can be seen from the many abandoned ponds due to crop failure. Even abandoned ponds on the island of Java reached 70%. This study used a quantitative method by collecting interview data and studying literature. Variables in this study include aquaculture (HR), technology, economic motives. The instrument used in this study was in the form of an interview sheet. and West Java p(T<=t) 0.2. Area of harvested land from Central Java and West Java Provinces with p=0.04 (<0.05). Yields from the provinces of East Java and Central Java with p=0.02 (<0.05). Area of harvested land from East Java and Central Java with p=0.04 (<0.05). Getting to the conclusion that there is a relationship between the area of harvested land and yields in the Provinces of East Java and West Java.